2018
DOI: 10.3390/su10041039
|View full text |Cite
|
Sign up to set email alerts
|

Social Sustainability in Apparel Supply Chains—The Role of the Sourcing Intermediary in a Developing Country

Abstract: After considering significant literature on sustainable supply chain management (SSCM), it is evident that research has neglected the social dimension and still lacks in highlighting the role of sourcing intermediaries in supply chains. The apparel supply chain has increased enormously in length and complexity, driving apparel retailers to employ sourcing intermediaries who manage their sourcing activities with suppliers from developing countries overseas. Thus, the purpose of this study is to enrich existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 98 publications
(409 reference statements)
3
26
0
Order By: Relevance
“…Nevertheless, the cases explicitly mentioned that sourcing agents cannot be monitored by western retailers on an permanent basis due to the spatial distance and respective monitoring costs, leaving effective social standard implementation at risk. This finding confirms prior findings that spatial distance increases information asymmetries [38,51,57].…”
Section: Hidden Intentionssupporting
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, the cases explicitly mentioned that sourcing agents cannot be monitored by western retailers on an permanent basis due to the spatial distance and respective monitoring costs, leaving effective social standard implementation at risk. This finding confirms prior findings that spatial distance increases information asymmetries [38,51,57].…”
Section: Hidden Intentionssupporting
confidence: 91%
“…However, researchers criticize the fact that the buyer's perspective and their first-tier supplier relationship has been investigated predominantly, while there is little known about how (lower-tier) suppliers perceive the social compliance strategies of their buyers [27,28]. Moreover, the sourcing agent as an intermediary between the buyer and the first-tier supplier has been neglected widely in multi-tier supply chain research, although researchers found that a sourcing agent assumes high responsibility for managing and ensuring the implementation of required social standards further upstream in the supply chain [57].…”
Section: Social Standards In Multi-tier Apparel Supply Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, exploitation of resources across globally dispersed supply chains often resulted in many environmental and social issues [9]. The collapse of the Rana Plaza factory in 2013 in Bangladesh [10][11][12][13], which caused thousands of deaths, placed the fashion industry under increasing public scrutiny and fashion companies felt the urgency of bridging the gap between economic sustainability and social and environmental performance [14]. Consequently, they are now trying to make their manufacturing sourcing more sustainable by focusing on the triple bottom line (TBL) approach, which involves the economic, environmental, and social dimensions of sustainability [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The industry also generates high social risks related to inhumane working conditions where production is outsourced to lower labor cost countries in order for organizations to remain competitive. In general, the implementation of processes to improve the sustainability of a company in the apparel industry is challenging due to the financial pressures on management for lower cost and shorter lead time [13], as well as the above stated features of a global industry. Each industry has different benefits for using RFID specific to their business models.…”
Section: Literature Reviewmentioning
confidence: 99%